Question
upstudy study bank question image url

Find each Derivative \( 41 y=\left(\frac{3 t^{2}-1}{3 t^{2}+1}\right)^{-3} \)

Ask by Henry Bradley. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( 41y = \left(\frac{3t^{2}-1}{3t^{2}+1}\right)^{-3} \) with respect to \( t \) is: \[ \frac{dy}{dt} = -\frac{36t (3t^{2} + 1)^{2}}{41 (3t^{2} - 1)^{4}} \]

Solution

We wish to differentiate   41y = [(3t² – 1)/(3t² + 1)]^(–3) with respect to t. We shall first solve for y and then differentiate. Step 1. Solve for y:   y = 1/41 · [(3t² – 1)/(3t² + 1)]^(–3) Step 2. Write y as a composition of functions. Let   u(t) = (3t² – 1)/(3t² + 1) so that   y = 1/41 · [u(t)]^(–3). Step 3. Differentiate using the chain rule. The derivative of u^(–3) with respect to u is –3u^(–4). Thus,   dy/dt = (1/41) · [–3u^(–4)] · u'(t)       = –3/(41) · u^(–4) · u'(t). Step 4. Find u'(t) using the quotient rule. Recall u(t) = f(t)/g(t), where   f(t) = 3t² – 1  and  g(t) = 3t² + 1. Their derivatives are:   f'(t) = 6t  and  g'(t) = 6t. The quotient rule gives:   u'(t) = [f'(t)g(t) – f(t)g'(t)] / [g(t)]²       = [6t(3t² + 1) – (3t² – 1)(6t)] / (3t² + 1)². Notice that both terms in the numerator have 6t:   = 6t[ (3t² + 1) – (3t² – 1) ] / (3t² + 1)²   = 6t[3t² + 1 – 3t² + 1] / (3t² + 1)²   = 6t(2) / (3t² + 1)²   = 12t / (3t² + 1)². Step 5. Substitute u'(t) back into the derivative for y:   dy/dt = –3/(41) · u^(–4) · [12t/(3t² + 1)²]       = –36t/(41) · u^(–4)/(3t² + 1)². Recall that u(t) = (3t² – 1)/(3t² + 1) so that   u^(–4) = [ (3t² – 1)/(3t² + 1) ]^(–4)       = [ (3t² + 1)/(3t² – 1) ]^(4). Substitute this in:   dy/dt = –36t/(41) · [ (3t² + 1)⁴/(3t² + 1)² · 1/(3t² – 1)⁴ ]       = –36t/(41) · (3t² + 1)^(4–2)/(3t² – 1)⁴       = –36t (3t² + 1)²/[41(3t² – 1)⁴]. Thus, the derivative is:   dy/dt = –36t (3t² + 1)² / [41 (3t² – 1)⁴].

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find the derivative of \( 41 y=\left(\frac{3 t^{2}-1}{3 t^{2}+1}\right)^{-3} \), we start by applying the chain rule and the quotient rule. First, let \( u = \frac{3 t^2 - 1}{3 t^2 + 1} \). Then, we need to find \( \frac{dy}{dt} \) as follows: Using the chain rule: 1. Differentiate \( y \) with respect to \( u \): \[ \frac{dy}{du} = 41 \cdot (-3) u^{-4} = -123 u^{-4} \] 2. Now, we differentiate \( u \) with respect to \( t \) using the quotient rule: \[ \frac{du}{dt} = \frac{(3 t^2 + 1)(6t) - (3 t^2 - 1)(6t)}{(3 t^2 + 1)^2} \] Simplifying this gives: \[ \frac{du}{dt} = \frac{6t[(3t^2 + 1) - (3t^2 - 1)]}{(3t^2 + 1)^2} = \frac{6t \cdot 2}{(3t^2 + 1)^2} = \frac{12t}{(3t^2 + 1)^2} \] Now, combine these results to find the derivative \( \frac{dy}{dt} \): \[ \frac{dy}{dt} = \frac{dy}{du} \cdot \frac{du}{dt} = -123 u^{-4} \cdot \frac{12t}{(3t^2 + 1)^2} \] Substituting \( u \) back in: \[ \frac{dy}{dt} = -123 \left(\frac{3t^2 - 1}{3t^2 + 1}\right)^{-4} \cdot \frac{12t}{(3t^2 + 1)^2} \] This will give the final derivative, and can be simplified further if necessary.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy